Open Access Publishing of Textbooks and Guidelines for Otolaryngologists in Developing Countries - Johannes J. Fagan MBChB, FCS (ORL), MMed (OTO Open, 2019)
Accessing educational and scientific material is key to improving otolaryngology care in developing countries. Yet current financial models of publishers restrict access to academic information. This article describes the author’s experience with self-publishing 2 open access textbooks, Open Access Atlas of Otolaryngology, Head and Neck Operative Surgery and Open Access Guide to Audiology and Hearing Aids for Otolaryngologists , as well as the African Head and Neck Society (AfHNS) Clinical Practice Guidelines for Head and Neck Cancer in Developing Countries and Limited Resource Settings . The author outlines the simplicity, advantages, and popularity of this form of publication and why societies and individuals should embrace open access publishing to benefit especially those studying and practicing in developing countries. He discusses some of the challenges related to open access publishing and calls for medical societies to become involved in evaluating the quality of open access texts and videos for their members.